Prevalence of probable substance use disorders among children in Ugandan health facilities - Harriet Aber-Odonga; Juliet Ndimwibo Babirye; Ingunn Marie S. Engebretsen; Fred Nuwaha (BMC, 2024)
Abstract Background Globally, there is a concerning surge in the prevalence of substance use among adolescents and children, creating a substantial public health problem. Despite the magnitude of this issue, accessing healthcare explicitly for substance use remains challenging, even though many substance users frequently visit healthcare institutions for other health-related issues. To address this gap, proactive screening for substance use disorders has emerged as a critical strategy for identifying and engaging patients at risk of substance use. The purpose of this study was to investigate the prevalence of probable alcohol and other substance use disorders, and associated factors, among children aged 6 to 17 years old attending health facilities in Mbale, Uganda. Methods We conducted a health facility cross-sectional study, involving 854 children aged 6-17 years. The prevalence of probable alcohol and other substance use disorders was assessed using a validated Car, Relax, Alone, Forget, Friends, Trouble (CRAFFT) screening tool. Univariable and multivariable modified Poisson regression analyses were performed using STATA 15 software. Results The overall prevalence of probable alcohol use disorders (AUD) and other substance use disorders (SUD) was 27.8% (95% CI 1.24-1.31) while that of probable AUD alone was 25.3% (95% CI 1.22-1.28). Peer substance use (APR = 1.24, 95% CI 1.10-1.32), sibling substance use (APR = 1.14, 95% CI 1.06-1.23), catholic caregiver religion (APR = 1.07 95% CI 1.01-1.13), caregiver income of more than $128 (APR = 0.90, 95% CI 0.82-0.98), having no parental reprimand for substance use (APR = 1.05, 95% CI 1.01-1.10) and having no knowledge of how to decline an offer to use substances (APR = 1.06, 95% CI 1.01-1.12) were found to be significantly associated with probable AUD/SUD. Conclusions Our findings suggest a high prevalence of probable AUD and SUD among children and adolescents visiting healthcare facilities for other conditions, along with a strong link between AUD and SUD prevalence and social factors. The implication for our healthcare system is to actively screen for and treat these conditions at primary healthcare facilities.